KOMUNIKASI DAN KOLABORASI DIGITAL DALAM LOKALISASI SDGS - Ditha; Seti Indriani, Sri (Jurnal Dakwah Tabligh, 2024)
Who would have thought that the existence of digital media could promote health to the public so quickly? Healthy and prosperous living is SDGs goal three also becomes information that circulates quickly if promoted through digital media. Is this true? Check the truth through various health communication events presented in this chapter. One of them is information about healthy living with herbs, as one of the health promotion programs by health workers who are experts in their fields. This is in line with Indonesia’s local cultural heritage attached to the ancestors’ tradition of using herbal plants. In addition, this phenomenon also illustrates an effort to localize the SDGs of healthy and prosperous living with herbs in Indonesia. This is interesting to study, especially in terms of knowing the efforts made to localize the SDGs of healthy living with herbs in Indonesia. Therefore, this chapter thoroughly explores the main keys in herbal health promotion programs in Indonesia, as well as unpacks the efforts to localize the SDGs of healthy living with herbs through digital collaboration & communication. The research method used is the case study method, with data collection techniques namely observation, literature study, and in-depth interviews. The results showed that the collaboration and digital communication found were diverse, ranging from the individual level and community level. Collaboration and digital communication are key in localizing the fourth point of Indonesia’s SDGs, namely healthy and prosperous living. In this research, healthy living with herbs is promoted as health promotion by health workers. The digital collaboration and communication in question are shown through the existence of health promotion through digital media in the form of various social media.